(untitled) (Third Sector Social Economic Review, 2017)
Abstract In the recent past, it can be observed that internet has provided business world competitive advantage. Currently internet technology has the power to revolutionize the business world. In this study, a recently trend topic in academic world, internet of things, is discussed. Firstly a general description of the concept is made. Then the concept is analyzed from business opportunities, productivity, profitability perspectives and discussed through SWOT analysis and analysis of potential business models. The first years of internet, Web 1.0, can be characterized as interconnected html documents. Web 2.0 enabled user interaction, cooperation and two way communication. In this era social network sites, blogs and wiki Technologies dominated. Although currently web 2.0 has been ruling, academicians have been targeting web 3.0. Internet of things stemming from industry 4.0 and the most advanced usage form of internet till today, has been used in home automation, healthcare, agriculture, banking, transportation and logistics. It is predicted that in the near future internet of things will ameliorate operational functions and customer experiences through certain improvements in each step of the action. Key Words: Internet of things, industry 4.0, internet technologies, web, new business models JEL Kodları: M15,M21,M54